If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4log(4x + 5) = -2 Reorder the terms: 4glo(5 + 4x) = -2 (5 * 4glo + 4x * 4glo) = -2 (20glo + 16glox) = -2 Solving 20glo + 16glox = -2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: 2 + 20glo + 16glox = -2 + 2 Combine like terms: -2 + 2 = 0 2 + 20glo + 16glox = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(1 + 10glo + 8glox) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(1 + 10glo + 8glox)' equal to zero and attempt to solve: Simplifying 1 + 10glo + 8glox = 0 Solving 1 + 10glo + 8glox = 0 Move all terms containing g to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 10glo + -1 + 8glox = 0 + -1 Reorder the terms: 1 + -1 + 10glo + 8glox = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 10glo + 8glox = 0 + -1 10glo + 8glox = 0 + -1 Combine like terms: 0 + -1 = -1 10glo + 8glox = -1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5x-1-3=2 | | 3b-4-3b/2 | | 9x+4=10x+3 | | Log[4](3X)=3 | | 8(4y)-9(y)+1=0 | | -25=2v-7 | | 7=-7(v+2) | | 5x+5+2x-2=-4 | | 64/8/2 | | (8d^5)/4d^-3 | | 38=3u-10 | | 2a=-(1-a) | | 10x+2=6x+42 | | 6X^3+60X^2+96X-160=0 | | -6x=24+18x | | 5w+9=54 | | 5x+1+2x-1=-4 | | 7(x+6)-9(9x-5)=15 | | 9(x+2)-2(x-8)=14 | | lnx=sqrt(8-lnx^2) | | -4n=-9 | | y=ln(x)+c | | Ax(x-1)+B(x+1)(x-1)+C(x+1)x=x^2+4 | | -4b=11 | | 8x+2=4x-24 | | 11-6= | | -34=-2(3x+5) | | 6f+5(4f+3)= | | 6(2n+8)=102 | | 107=107(47-y) | | 4(3n-3)=48 | | 2x^2+25x+20=-x^2-8 |